PSYCHOLOGICAL TRAINING OF BASKETBALL PLAYERS AT CYSS (Physical Culture and Sport: Scientific Perspective, 2025)
The paper theoretically substantiates the influence of CYSS on the psychological training of young basketball players, reveals the basic theoretical principles of psychological training in the educational and training process, and improves the results of basketball players. It is emphasized that CYSS are able to educate a personality, form a healthy lifestyle, strengthen its health and enrich its motor potential.The formed team of the training group of a children's and youth sports school takes on a significant educational function. The training group of the CYSS is pedagogically organized, and this not only helps the athlete to learn positive roles in society (such as a team member), but also reduces the risk of acquiring negative roles (drug addict, thief, etc.). This group contributes to the education and development of a sports leader. As a result of self-organization, young basketball players develop relationships of dominance and subordination, influence, respect and imitation. The psychological training of basketball players in the CYSS is aimed at developing the mental qualities necessary to achieve high sports results. The goal of such training is to create sustainable motivation, build self-confidence, overcome stress and emotional instability, and develop team spirit.The peculiarities of pupils of different age groups are noted: at the age of 16-17, maturation is completed and the skeleton becomes stronger, muscle strength increases, and a person can withstand heavy loads. There is a general maturation of the body. This is the period of formation of worldview, beliefs, character and outlook on life. Adolescents usually have a pronounced selective attitude to academic subjects, which is one of the most characteristic features of modern adolescents. This characterizes the development and functioning of mental processes. Basketball players of this age feel and respect intellectual qualities and knowledge. Young basketball players develop the ability to comprehensively assess a person and the situation of the mold. It is noted that young years are one of the most favorable periods of life in psychological education and development of physical qualities of a person.In adolescence, the number of roles played in society increases, the requirements for responsibility for actions and deeds increase, self-determination is formed, the ability to achieve goals and objectives is improved, young athletes become more independent; the process of forming a value orientation towards social activity continues.
Keywords: psychological training; young basketball players